Protocol for Comparing the Efficacy of Three Reconstruction Methods of the Digestive Tract (Kamikawa Versus Double-Tract Reconstruction Versus Tube-Like Stomach) After Proximal Gastrectomy - Wang, Wei Dong; Gao, Rui Qi; Chen, Tong; Dong, Dan Hong; Yang, Qin Chuan; Zhou, Hai Kun; Wei, Jiang Peng; Yu, Peng Fei; Yang, Xi Sheng; Li, Xiao Hua; Ji, Gang (Frontiers in Surgery, 2022)
Background Appropriate gastrointestinal reconstruction after proximal gastrectomy can effectively reduce the incidence of postoperative complications in patients with proximal early gastric cancer. However, there is still great controversy about the choice of digestive tract reconstruction after proximal gastrectomy, and there is no clinical consensus on the choice of digestive tract reconstruction after proximal gastrectomy. Currently, there is a lack of large-sample, prospective, randomized controlled studies to compare the efficacy of Kamikawa, double-tract reconstruction, and tube-like stomach reconstruction after proximal gastrectomy. Methods/design This study will investigate the efficacy of three reconstruction methods after proximal gastrectomy in a prospective, multicenter, randomized controlled trial, which will enroll 180 patients with proximal early gastric cancer. Patients will be randomly divided into three groups: Group A (Kamikawa, n = 60), Group B (double-tract reconstruction, n = 60), and Group C (tube-like stomach, n = 60). The general information, past medical history, laboratory findings, imaging findings, and surgical procedures of the patients will be recorded and analyzed. The incidence of reflux esophagitis will be recorded as the primary endpoint. The incidence of anastomotic leakage, anastomotic stenosis, operative time and intraoperative blood loss will be recorded as secondary endpoints. Discussion This study will establish a large-sample, prospective, randomized controlled trial to compare the efficacy of Kamikawa, double-tract reconstruction, and tube-like stomach reconstruction after proximal gastrectomy. Trial registration This study was approved by the Chinese Clinical Trial Registry and registered on April 30, 2021. The registration number is ChiCTR2100045975.